Populasi dan Aktivitas Mikroorganisme Rhizosfer Kedelai pada Entisol Akibat Pemberian Bahan Organik dan Pupuk Hayati - Yusnizar Yusnizar; Hifnalisa Hifnalisa; Fikrinda Fikrinda (Fakultas Pertanian, Universitas Syiah Kuala, 2006)
The Microorganism Population and Activity in the Rhizosphere of Soybean on Entisol caused by Some Organic Matter and BiofertilizerABSTRACT. The entisol productivity can be increased by using the organic matter as the organic fertilizer for example the waste oil palm (especially the empty fruit bunches of the oil palm) and the manure. Beside this, the Entisol productivity can be increased with used the biofertilizer for example Rhiphosant. Using the organic fertilizer and the biofertilizer also effect the microorganism population and activity in the rhizosphere. The objective of this research as to evaluate the microbial population and activity in the rhizosphere of the soybean as affected the organic matter and the biofertilizer on Entisol. This research was set up according to Factorial Randomized Block Design, there were the organic matter and the biofertilizer. Kind of the organic matter no the organic matter. the was oil palm, the manure, and the was oil palm + manures. Kind of the biofertilizer were without the biofertilizer and with the. There were 8 trial combinations with 3 replications so there were 24 experimental units. The parameters observed were the microorganism population and activity at 45 Days After Planting (DAP); The population of the total microorganism, bacteria, fungi, phosphate solubilizing microorganisms, rhizobium, and microorganism activity. Result of this study show that the first and the second factor were not significant to all parameters. Interaction between the organic matter with the biofertilizer only effected significantly to the fungi population.